KEPEMIMPINAN DI MEDAN TEMPUR: TANGGUNG JAWAB KOMANDO DALAM PENEGAKAN HUKUM HUMANITER INTERNASIONAL - Adam Tjahja S; Frans Eddy Bungaran Siregar, Tarsisius Susilo, Wahyudi Dwi Santoso, Nurhidayat (INTELIGENSIA MEDIA, 2025)
Command responsibility is a key doctrine in international humanitarian law (IHL) requiring military leaders to be held accountable for crimes committed by subordinates if they fail to prevent or punish such acts. This article analyzes the theory and practice of command responsibility in the context of Indonesian military leadership. The abstract briefly outlines historical development of the doctrine (from the 1863 Lieber Code to the 1998 Rome Statute), its adoption into Indonesian law (Law No. 26/2000 on human rights courts), and differences between international and national application. The study examines the elements of command responsibility (superior-subordinate relationship, knowledge or “should have known,” and duty to take reasonable measures) and surveys international case law (e.g. the Celebici case in ICTY and the Jean- Pierre Bemba case in ICC). It then addresses Indonesian scenarios (military operations in East Timor and Papua), domestic human rights trials, and TNI contributions to UN peacekeeping and IHL training. Contemporary challenges (drone warfare, cyber attacks, hybrid warfare) and their implications for commander responsibility are discussed. The paper concludes that embedding IHL values in TNI command structures enhances the legitimacy and effectiveness of Indonesian military leadership. Recommendations focus on strengthening IHL training, clarifying command rules, and harmonizing national law with international standards to ensure consistent enforcement of command responsibility.